Thermal Efficiency Analysis on Box Dryer Equipment in the Chemical Industry - Savitri, Melisa Dwi; Sari, Dessy Agustina; Hakiim, Azafilmi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
Box dryers are widely utilized in the chemical processing, food, and agricultural industries for drying purposes. The efficiency of these dryers significantly impacts energy utilization. Low thermal efficiency suggests inefficient heat utilization compared to the energy required for drying. Therefore, analyzing thermal efficiency is crucial to optimize energy usage, enhance drying effectiveness, and identify avenues for improvement. This study employs a direct method to assess the thermal efficiency of a box dryer. Data from observations, operational parameters, and literature form the basis for calculating thermal efficiency. Results indicate thermal efficiency ranging from 89.00% to 92.00%, with a drying feed mass rate of 77–91 kg/hour over six hours of operation. These findings classify the box dryer equipment as highly efficient. The industry maintains this efficiency through periodic maintenance schedules and optimization of drying conditions. This research provides a foundational analysis of box dryer performance, aiming to streamline the drying process and minimize energy consumption. The outcomes contribute to ongoing efforts in industrial sectors to enhance operational sustainability and economic viability.